Effect of different storage methods on germination and seedling emergence of six pawpaw (Carica Papaya L.) varieties planted in Ogbomoso, Oyo state, Nigeria - Olayiwola SA; Olaniyi JO; Alamu LO; Lawal SW (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2023)
Pawpaw is known as a fruit that contains nutrients and vitamins ranging from green ripe to over-ripe and unripe fruits of various varieties. The poor and delayed germination, rapid loss of viability in seeds due to the presence of sarcotesta, and condition of storage of seeds could be addressed through the storage in various containers. This paper focused on the investigation of the best storage methods that aid germination, seedling emergence and seedling performance of six pawpaw varieties. The experiment was set up in the Crop and Soil Science Laboratory Department and Nursery Site of the Ladoke Akintola University of Technology, Ogbomoso (Oyo-State). It was a 6 x 5 factorial experiment that consisted of 6 varieties of pawpaw; Pink Solo, Green Solo, Ghana Solo, Sunrise Solo, Ajawa Local, and Berry likewise the 5 storage methods are desiccator, refrigerator, plastic container, aluminum foil paper, and earthen pot. Data were collected by counting the number of germinated seeds manually from 4 - 16 days after sowing inside Petri dishes, emergence rate was also counted after seeds have been sown inside polythene bags and nursed for 12 weeks and the number of seeds germinated and seedling emergence was transformed into percentages. Seedling emergence rates were also counted manually and analysed by using Analysis of Variance (ANOVA), means were compared using the least significant difference at a 5% probability level. Significant differences were observed among storage methods and pawpaw varieties in germination rate, seedling emergence, and performance. The highest plant height was observed in green solo at 12WAS in the nursery (25.63 cm), the highest stem girth was recorded in Ajawa local 3.86 cm while the highest number of leaves was recorded in sunrise 9.9. The total emergence percentage was recorded in Green Solo at 93.8%. The highest germination percentage was observed in Ghana Solo 59.4%. The highest germination, seedling emergence, plant height, and number of leaves were recorded in the desiccator as 44.96%, 84.4%, 23.32 cm, and 9.38. Ajawa Local and Green Solo are recommended to be kept inside a desiccator or plastic container.